2015
DOI: 10.1249/jsr.0000000000000206
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Weight Loss in Sports with Weight Classes

Abstract: Weight-sensitive sports are popular among elite and nonelite athletes. Rapid weight loss (RWL) practice has been an essential part of many of these sports for many decades. Due to the limited epidemiological studies on the prevalence of RWL, its true prevalence is unknown. It is estimated that more than half of athletes in weight-class sports have practiced RWL during the competitive periods. As RWL can have significant physical, physiological, and psychological negative effects on athletes, its practice has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(91 citation statements)
references
References 21 publications
5
72
1
1
Order By: Relevance
“…The most frequent methods used by judo players were increased exercise, restricted food ingestion, training in heated rooms, gradual dieting, and fluid restriction [7]. In accordance with several reports our results showed that rapid Weight loss affects negatively performance in judo athletes [41]. We herein argue that rapid Weight loss clearly meets all three criteria and, therefore, should be banned from the sport [42], Considering that these health-threating methods are more commonly used by lower level athletes, specific education programs should be directed to them [43].…”
Section: Discussionsupporting
confidence: 91%
“…The most frequent methods used by judo players were increased exercise, restricted food ingestion, training in heated rooms, gradual dieting, and fluid restriction [7]. In accordance with several reports our results showed that rapid Weight loss affects negatively performance in judo athletes [41]. We herein argue that rapid Weight loss clearly meets all three criteria and, therefore, should be banned from the sport [42], Considering that these health-threating methods are more commonly used by lower level athletes, specific education programs should be directed to them [43].…”
Section: Discussionsupporting
confidence: 91%
“…Education and advocacy efforts have been used to attempt to change this perception, and although the effects have been largely positive, unsafe cultural norms reflecting incorrect information persist in some settings. 33 When the socioecological framework was redefined by McLeroy et al 9 in 1988, the environmental level also included the physical environment, such as access to parks and transportation. In sports medicine, the environmental level may also refer to the actual environmental and playing-field conditions, and interventions can be designed to directly address these factors (eg, cancel activity during extreme weather, ensure playing conditions are safe).…”
Section: Environmental Factorsmentioning
confidence: 99%
“…Rapid weight loss is an act of losing weight in a short time to reach the standard necessary to compete in a specific weight class. It is characterised as transitory weight loss of no less than 5% of one's weight within a short period of time (a week) [8]. In some situations, RWL can be practised as late as the day before the competition.…”
Section: Introductionmentioning
confidence: 99%